Body Weight and Morphometric Characteristics of KUB Chicken at 60 Days of Age - Al Farizi, Muhammad Salman; Jan, Rahma; Maskur, Maskur; Rozi, Tapaul; Muhsinin, Muhammad (Jurnal Biologi Tropis, 2024)
Kampung Unggul Balitnak Chicken (KUB) is a highly favored Indonesian native chicken breed among breeders because of its rapid development rate and ability to thrive in many situations. This study aimed to investigate KUB chickens' growth performance and morphometric parameters at 60 days of age, a crucial phase for determining their suitability as commercial broilers. Using an intensive rearing system, 100 KUB chickens were reared for 60 days in group cages. Body weight measurements were recorded weekly, and morphometric traits were measured after the study period. The study's findings indicated that the mean body weight of KUB chickens at 60 days of age was 710.53±16.76 grams, suggesting a favorable growth rate. In addition, the morphometric analysis revealed favorable physical characteristics, including an average chest length of 100.55±3.70 mm, chest width of 47.47±3.12 mm, wing length of 165.93±4.34 mm, back length of 164.9±4.26 mm, back height of 205.51±3.99 mm, shank length of 63.23±3.69 mm, and shank circumference of 35.76±1.48 mm. The results indicate that KUB chickens exhibit desirable body weight and morphometric traits at 60 days old, proving their suitability in commercial broiler farming. To summarize, this study offers significant information regarding the growth performance and physical characteristics of KUB chickens during a critical phase of their development. The findings highlight the breed's capacity to serve as a practical choice for commercial broiler production, enhancing the variety and long-term viability of the poultry sector in Indonesia.